CLINICAL SPECTRUM AND MANAGEMENT OF OVARIAN TUMOURS IN YOUNG GIRLS UPTO 20 YEARS OF AGE - Baloch, Shahla; Khaskheli, Meharunnissa; Malik, Arshad Mehmood; Sheeba, Aneela; Khushk, Imdad A. (Journal of Ayub Medical College Abbottabad, 2008)
Background: Ovarian tumours are one of the common malignancies all over the world affecting all age groups. This study analyses different clinical presentation and management of ovarian tumours in young girls up to 20 years. Methods: Patients up to 20 years of age admitted with the diagnosis of ovarian tumour were included. Data collected on a proforma. Variables studied included age, presenting symptoms, investigations, surgical findings, type of surgery, histopathology reports and follow-up. The patients with malignant ovarian tumour were followed by oncologist as well as gynaecologist. Data analysis was done on SPSS. Results: The mean age was 17.27±2.46 SD years. The common symptoms included abdominal mass, abdominal pain, urinary problems, menstrual irregularities and generalized malaise. All patients were operated after preliminary investigations. Patients were advised to have follow-up post-operatively after 1 month. The follow up was done by oncologist and gynaecologist. Six patients (12.5%) died and 22 (45.83%) were lost to follow up. Conclusion: Ovarian tumours are quite common in young girls. Majority of patients seek medical advice once the disease becomes symptomatic, complicated or advanced disease in the case of malignancy. Histopathology of the tumours revealed that epithelial cell tumour is the commonest tumour in contrast to germ cell tumour as reported by world literature. Keywords: Ovarian tumours, Young age, Conservative surgery, Teratoma, Neoplasm